2021
DOI: 10.1016/j.ekir.2021.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Kidney Function in CKD of Uncertain Etiology

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Also known as CKD of non-traditional cause, chronic interstitial nephritis in agricultural communities, Mesoamerican nephropathy and Uddanam Nephropathy, CKDu has been observed largely in the Global South, including India, Sri Lanka, parts of Africa, and Central and South America 49,51,52 . One study of people with CKDu in India found worsening of metabolic acidosis and hypertension in summer compared with winter, supporting the hypothesis that a warming planet also threatens kidney health 50 . Increasing salinity of drinking water in coastal areas of Bangladesh affected by rising sea levels has also been linked to increased rates of preeclampsia and gestational hypertension, in addition to hypertension and albuminuria in the general population, all of which are risk factors for subsequent kidney disease [53][54][55] .…”
Section: Environmental and Social Threats To Kidney Health Continue T...mentioning
confidence: 91%
See 1 more Smart Citation
“…Also known as CKD of non-traditional cause, chronic interstitial nephritis in agricultural communities, Mesoamerican nephropathy and Uddanam Nephropathy, CKDu has been observed largely in the Global South, including India, Sri Lanka, parts of Africa, and Central and South America 49,51,52 . One study of people with CKDu in India found worsening of metabolic acidosis and hypertension in summer compared with winter, supporting the hypothesis that a warming planet also threatens kidney health 50 . Increasing salinity of drinking water in coastal areas of Bangladesh affected by rising sea levels has also been linked to increased rates of preeclampsia and gestational hypertension, in addition to hypertension and albuminuria in the general population, all of which are risk factors for subsequent kidney disease [53][54][55] .…”
Section: Environmental and Social Threats To Kidney Health Continue T...mentioning
confidence: 91%
“…This condition is characterized by the presence of a benign urinary sediment and tubulointerstitial changes on biopsy 47 . Proposed mechanisms include recurrent heat stress with repeated episodes of AKI and exposure to environmental toxins, including pesticides and heavy metals [48][49][50][51] . Also known as CKD of non-traditional cause, chronic interstitial nephritis in agricultural communities, Mesoamerican nephropathy and Uddanam Nephropathy, CKDu has been observed largely in the Global South, including India, Sri Lanka, parts of Africa, and Central and South America 49,51,52 .…”
Section: Environmental and Social Threats To Kidney Health Continue T...mentioning
confidence: 99%